Comparative in vitro rumen fungal degradation and gas production of cellulosic feeds in cattle and buffalo - SANGWAN, D C; KUMAR, SHIV; BHATIA, S K; SINGH, SADHANA (The Indian Journal of Animal Sciences, 2014)
Ruminal degradations (in vitro) of DM and fibrous components in 9 substrates, besides gas production profile by anaerobic fungi which were compared in cattle and buffalo were influenced (P